The image of an eagle in the story of Shukur Kholmirzaev - Koziyeva Shahrizoda (Peerian Journals Publishing, 2022)
In the story "Bandi Burgut" by Shukur Kholmirzaev, the article discusses the suffering of an eagle who fought for freedom, whose parents died far away from his relatives, in captivity, in the way of freedom
Keywords: Freedom; eagle; captivity; environment